Effects of fish protein hydrolysate on the growth performance, feed and protein utilization of Nile tilapia (Oreochromis niloticus) - Khieokhajonkhet, A.; Surapon, K. (International Journal of Agricultural Technology, 2020)
The effect of fish protein hydrolysate (FPH) supplementation on the growth performance, feed and protein utilization and feeding cost of Nile tilapia (Oreochromis niloticus) was determined. Juvenile Nile tilapia were randomly distributed into five groups and fed with five isonitrogenous (32% crude protein) and isolipidic (7% crude fat) diets. The control diet contained fish meal without FPH supplementation (basal diet). Diets 2-5 contained 10% and 30% oil layer protein hydrolysate (OLPH) and 10% and 30% of aqueous protein hydrolysate (APH), respectively. All experimental fishes were manually fed to apparent satiation in triplicate groups for 8 weeks. Fish fed with APH10 diet had significantly higher growth performance (P < 0.05) in terms of final fish body weight, weight gain, average daily gain (ADG) and specific growth rate (SGR). In addition, fishes fed with APH10 had significantly higher feed utilization, protein efficiency ratio (PER) and protein productive value (PPV) than the fishes fed with the other diets (P < 0.05). The diet containing over 10% APH caused a reduction in growth performance, feed and protein utilization, possibly resulting from the high small peptides and amino acids which were over the appropriate range for dietary protein requirements for Nile tilapia. The cost of APH10 diet exhibited 26 bahts per kg fish gain in weight, it was lower than all other test diets. Our current finding indicates that dietary APH10 could improve growth performance, feed efficiency, protein utilization, and beneficial feeding cost for Nile tilapia.